The Effects of Perception on Teacher Guidance and Motivation towards Students' Indonesian Learning Achievement - Lilis Surtini (Universitas Indraprasta PGRI, 2022)
Research on the factors that influence the achievement of learning Indonesian has been done by many previous researchers. The purpose of this research is to find out 1). The effects of perceptions of teacher guidance and learning motivation towards students' Indonesian learning achievement at State Junior High School (SMPN) Depok City. 2). The effect of perceptions of teacher guidance towards students' Indonesian learning achievement at State Junior High Schools (SMPN) Depok City. 3). The effect of learning motivation towards students' Indonesian learning achievement at State Junior High School (SMPN) Depok City. The methode used in this study is a survey with multiple linier regression correlational techniques with a sample of 40 students. The results of the study show: 1). There are a significant effect of Perception on Teacher Guidance and Learning Motivation together towards Learning Achievement of Indonesian Junior High School students in Depok City. This can be proven by the value of Sig. 0.000 < 0.05 and F-count = 39.115. 2). There is a significant influence on the perception of teacher guidance towards the achievement of learning Indonesian in State Junior High School students in Depok City. This can be proven by the value of Sig. 0.005 < 0.05 and t-count = 2,993. 3). There is a significant effect of learning motivation towards the achievement of learning Indonesian in State Junior High School students in Depok City. This can be proven by the value of Sig. 0.028 < 0.05 and t-count = 2.284Keywords: perceptions of teacher guidance, learning motivation, students' Indonesian learning achievement